Assessing spatiotemporal variations and predicting changes in ecosystem service values in the Guangdong–Hong Kong–Macao Greater Bay Area. Issue 1 (31st December 2022) - Zhang, Jie; Li, Xuecao; Zhang, Chenchen; Yu, Le; Wang, Jingzhe; Wu, Xiangyin; Hu, Zhongwen; Zhai, Zihan; Li, Qingquan; Wu, Guofeng; Shi, Tiezhu
ABSTRACT: Rapid economic development and interference by human activities in rapid urbanization regions have caused great land use/land cover change (LUCC), which significantly affects ecosystem functions and services. It is crucial to assess the spatiotemporal evolution of ecosystem service value (ESV) in such regions, especially for the Guangdong–Hong Kong–Macao Greater Bay Area (GBA) in China. In this study, we investigated and predicted the effect of LUCC on the ESV in the GBA from 1990 to 2030 using the latest annual 30 m LUCC database of China, the future land use simulation (FLUS) model, and ecosystem service evaluation approaches. The study period was divided into the historical period (1990–2015) and the forecast period (2015–2030). The results showed that forest and cropland were the dominant land-use types (>77% of the GBA), and the expansion of built-up land (3822.4 km 2 ) was the clearest process during 1990–2015. The reduction of cropland and forest contributed the most to the decrease in the total ESV. Moreover, the results confirmed that the FLUS model is effective at predicting future LUCC in the GBA. The ESV was predicted to decrease to 4962.23 × 100 million yuan in the 2030s under the current development mode if regional forest and waterbody reductions are not constrained. This study provides a reference for promoting the rational use of land resources and ecological construction in the GBA and can help to promote ecological planning and environmental protection.